Assessment of psychopathological problems in school context: the psychometric properties of a portuguese version of the adolescent psychopathology scale – short form - Lemos, Ida (2018)
The psychometric properties of a Portuguese version of the Adolescent Psychopathology Scale-Short Form (APS-SF) were studied in a sample of 656 Portuguese adolescents, aged 12 to 19 years, assessed in school context. Also, the aim of the study was to gather data concerning age- and gender-related differences in the expression of psychopathological problems assessed by the APS-SF. Results of the reliability of APS-SF scales are compared with those obtained by Reynolds in the validation studies with the American sample. Factor analysis reproduced the bidimensionality of the original validation studies of the scale. These findings seem to support the use of the APS-SF as a valuable tool for early identification of psychosocial problems in the school context in Portuguese adolescents. Results concerning age- and gender-related differences in the expression of psychopathological problems in the adolescents are discussed.